2016
DOI: 10.1007/s10901-016-9523-4
|View full text |Cite
|
Sign up to set email alerts
|

Informal settlement upgrading and safety: experiences from Cape Town, South Africa

Abstract: Informal settlement dwellers are disproportionately affected by ill health, violence and many other socioeconomic challenges. These are largely connected to the unhealthy and unsafe physical conditions within which they live. Interventions in the built form through the provision of physical infrastructure have been proposed as a strategy to improve economic, social and health outcomes for informal settlement dwellers and are also suggested as tools to address violence and insecurity, which have reached unprece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 10 publications
(11 reference statements)
0
31
1
Order By: Relevance
“…Apart from interventions that address alcohol use and drinking environments of people of low SES, socioeconomic differences can be addressed on a structural level [ 4 ]. Healthy communities require living environments with affordable housing, clean water, sanitation and electricity, infrastructure and public transit, access to education and healthcare, and safe opportunities to spend leisure time [ 78 , 79 ]. Marmot et al suggested that “ health and health equity might not be the aim of all social and economic policies, but they will be a fundamental result ” ([ 79 ], p. 1661).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from interventions that address alcohol use and drinking environments of people of low SES, socioeconomic differences can be addressed on a structural level [ 4 ]. Healthy communities require living environments with affordable housing, clean water, sanitation and electricity, infrastructure and public transit, access to education and healthcare, and safe opportunities to spend leisure time [ 78 , 79 ]. Marmot et al suggested that “ health and health equity might not be the aim of all social and economic policies, but they will be a fundamental result ” ([ 79 ], p. 1661).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless a necessary but not sufficient set of conditions for a neighborhood to be a slum deals with the lack of public street accesses, basic services, addresses and the availability of emergency services. For all these reasons -in resonance with processes of reblocking initiated by resident communities and local authorities [40,41] seen for Freetown and Monrovia. While this approach is not meant to be a substitute to traditional urban planning, it provides residents, planners and policy makers with new insights and proposals that promote gradual upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…They are continually shaped, transformed and re-constituted, both as a consequence of and a cause of conflict, competition and negotiation [37]. The rationale behind why and how things function as they do, or appear to do, may not be clear to an outsider, but they make sense to people living within the arrangements in the settlement [38].…”
Section: Hybrid Governance and Informal Settlement Land Administrationmentioning
confidence: 99%
“…In general, there are differing opinions between different branches and individuals within local planning and development authorities on how to go about informal settlement upgrading. Importantly, a number of officials are opposed to incremental approaches [38,49]. Abrahams observes the importance of involving all the affected departments in a city in low income housing and in situ informal settlement development.…”
Section: Informal Settlement Upgradingmentioning
confidence: 99%